Clinical Significance in Previously Healthy Children of Pseudomonas aeruginosa in the Stool - Ya-Lin Cheng; Hung-Chang Lee; Chun-Yan Yeung; Wai-Taow Chan (Elsevier, 2009)
Pseudomonas aeruginosa are normal flora in the human gastrointestinal (GI) tract, which on occasion cause GI tract infection. Methods: We evaluated the clinical significance of a pure growth of P. aeruginosa in fecal specimens in previously healthy children. The records of 45 previously healthy children under 15 years of age who were seen between June 2000 and August 2006 and who had a pure growth of P. aeruginosa in the stool were retrospectively reviewed. Results: Of the 45 children, 28 (62%) were infants, three of whom developed sepsis secondary to the pseudomonal infection; two of which died. Complications in another four included colonic perforation (in two), necrotizing enterocolitis (in one), and an anal ulcer resulting in anal stricture (in one). The seven children with complications were all infants. Although not all children in our study had complete data in laboratory determinations, the presence of bandemia, elevated C-reactive protein (CRP), anemia and hypoalbuminemia may be of clinical importance. Conclusion: P. aeruginosa growing in the stool of otherwise healthy children may indicate actual infection by the organism and may be associated with severe or even fatal disease, particularly in infants. Bandemia, elevated CRP, anemia, and hypoalbuminemia give further warning in these patients.